ANALISIS PENGARUH USER EXPERIENCE (UX) TERHADAP SCREEN TIME PENGGUNA MOBILE LEGENDS MENGGUNAKAN ALGORITMA LINEAR REGRESSION - ANGGRAENI, RITA FITRI; ABDURAHMAN , DEDE (Universitas Majalengka, 2025)
The use of mobile games such as Mobile Legends continues to grow among teenagers and young adults, leading to increased screen time. One factor that is thought to influence the duration of use of the app is user experience (UX). This study aims to analyze the impact of UX on Mobile Legends users' screen time. The approach applied is quantitative with a survey method through questionnaire distribution to 60 respondents who actively play Mobile Legends. The data obtained was then analyzed using a linear regression algorithm with the help of SPSS (Statistical Package for the Social Sciences) software to understand the relationship between UX and screen time. The findings indicate that UX influences the length of app usage, where the better the user experience, the higher the tendency for users to spend time playing. The study concludes that UX is an important element that influences the screen duration behavior of mobile game users, so this aspect should be considered in app development.